(untitled) (Bangladesh Journal of Agricultural Research, 2007)
A field experiment was conducted to study the effects of mulching and pruning in pear (cv. BARI Naspati-1) with two levels of mulching (mulched and non-mulched) and four levels of pruning (0, 25, 50, and 75 percent) at the Agricultural Research Station, Raikhali, Rangamati Hill District during 1999 to 2001. Mulching, pruning levels and their interaction showed significant effect on yield and some yield components of pear. Mulching in combination with 50% pruning gave the highest number of fruits (151) per plant and the highest fruit yield (20.87 t/ha). Percentage of total soluble solid (TSS %) increased with the increasing of pruning intensity with mulching. 75% pruning intensity with mulch gave the highest TSS (13.73%) followed by 50% pruning with mulch (13.51%). The combination of 50% pruning and mulching treatment gave the highest gross return (Tk. 758,000/ha) as well as gross margin (687, 000/ha) with maximum benefit-cost ratio (10.60). Bangladesh J. Agril. Res. 32(2) 2007: 225-233.